What can we learn about women’s empowerment in water, sanitation, and hygiene (WASH) in Malawi? Findings from the new Women’s Empowerment metric for WASH (WE-WASH) - Ramani, Gayathri V.; Faas, Simone; Chiwasa, Febbie; Chilalika, Joan; Kamwamba-Mtethiwa, Jean; Heckert, Jessica; Raghunathan, Kalyani (International Food Policy Research Institute, 2024)
Water, sanitation, and hygiene (WASH)-related challenges around the world can negatively affect communities and individuals, but people in resource-constrained areas face additional obstacles in preventing and recovering from the consequences of inadequate WASH infrastructure. WASH interventions in low and middle-income countries (LMICs) often target women as key actors for achieving project outcomes and many aim to improve the quality of women’s lives; fewer, however, have a specific focus on empowering women. A systematic review concluded that studies within the WASH sector have rarely focused specifically on empowering women, despite efforts to reach and benefit them (Caruso et al. 2022). In a review of gender-sensitive WASH indicators that have been used in the peer-reviewed literature, gray literature, and toolkits from organizations operating in WASH, only around 10% of the 162 indicators identified specifically measured empowerment.